WILLINGNESS TO PAY (WTP) OF TOURIST VISITORS SARASAH AIE LULUIH, SARASAH BUNTA, AND SARASAH MURAI - Sovia Anggraini; Noril Milantara; Hernawati Hernawati; Neni Marlina (Universitas Muhammadiyah Palembang, 2025)
A Nature Tourism Park (TWA) is a type of conservation area. In addition to functioning as a conservation area, TWA also functions as a tourist attraction. Harau Valley is one of the favorite tourist attractions in West Sumatra Province. The Sarasah Bunta area has three waterfalls in the same landscape, namely Sarasah Aie Luluih, Sarasah Bunta, and Sarasah Murai. This study aims to determine the factors that influence the Willingness to Pay (WTP) of visitors to the Harau Valley Waterfall, determine the amount of Willingness to Pay (WTP) of visitors to enjoy the Harau Valley Waterfall tour, and compare the Willingness to Pay (WTP) values of tourists at the three Harau Valley Waterfalls. The data used in this study include primary data and secondary data. This study used a multiple linear regression analysis approach, the Contingent Valuation Method (CVM), and descriptive analysis. The results of this study indicate that the WTP values that have a significant influence are income level at Sarasah Aie Luluih, education level at Sarasah Bunta, and gender at Sarasah Murai. The average WTP value of willingness to pay at each waterfall is IDR 6,625.00 per entry at Sarasah Aie Luluih, IDR 7,906.25 per entry at Sarasah Bunta, and IDR 7,233.33 per entry at Sarasah Murai. The Total WTP value (TWTP) is IDR 6,123,812,816.28 with an estimated visitor count of 281,366 people in the Harau Valley. Overall, differences in location, facilities, and atmosphere of each waterfall create different visitor segmentations, so that tourism management and development at the three locations are adjusted to the characteristics of visitors to each waterfall.